2020
DOI: 10.1123/jpah.2019-0381
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Physical Activity and Executive Functions Among Children: A Cluster Randomized Controlled Trial of an After-School Program in Australia

Abstract: Background: The aim of this study was to examine the efficacy of an embedded after-school intervention, on promoting physical activity and academic achievement in primary-school-aged children. Methods: This 6-month, 2-arm cluster randomized controlled trial involved 4 after-school centers. Two centers were randomly assigned to the intervention, which involved training the center staff on and implementing structured physical activity (team sports and physical activity sessions for 75 min) and academic enrichmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…These findings suggest that perhaps a longer follow-up period is necessary to identify changes in physical activity adherence. Overall, our findings and previous studies that have investigated team sport-based ( Veldman et al, 2020 ; Weintraub et al, 2008 ) and free or organized play ( Trost et al, 2008 ) on objectively measured children’s physical activity, suggest that these programs can increase time spent in MVPA and thus contribute to improvements in physical health markers.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…These findings suggest that perhaps a longer follow-up period is necessary to identify changes in physical activity adherence. Overall, our findings and previous studies that have investigated team sport-based ( Veldman et al, 2020 ; Weintraub et al, 2008 ) and free or organized play ( Trost et al, 2008 ) on objectively measured children’s physical activity, suggest that these programs can increase time spent in MVPA and thus contribute to improvements in physical health markers.…”
Section: Discussionsupporting
confidence: 77%
“…To attenuate the adverse effects of the trifecta of inactivity, sedentary behavior, and adiposity, many researchers and stakeholders, have made a conscious effort to identify strategies to increase children’s daily physical activity, especially in education environments such as schools and daycares ( Beets et al, 2009 ; Grao-Cruces et al, 2019 ; Kriemler et al, 2011 ; Mazzucca et al, 2018 ; Nagpal et al, 2020 ; Van Sluijs et al, 2007 ). Approximately half of Canadian children (47.5%) and nearly 20% of American children attend an afterschool program following each school day ( Afterschool Alliance, 2014 ; Statistics Canada, 2015a ) and a strategy that has gained traction within the research community is increasing children’s physical activity within the afterschool activity program (ASAP) setting ( Beets et al, 2009 ; Beets et al, 2010 ; Gesell et al, 2013 ; Veldman et al, 2020 ). Modifying ASAPs to be oriented/focused around physical activity has been encouraged in place of the more traditional sedentary activities, including homework club, computer club, watching television, and doing seated arts and crafts ( Beets et al, 2010 ).…”
mentioning
confidence: 99%
“…In an effort to meet students' needs for health the mental and physical benefits of sports and exercise, including improved cognitive function, emotional regulation, interpersonal competence, and ethical decision-making, table tennis learning activities which so far have only been taught by teachers through lecture and practice methods, one way to overcome this is the implementation of follow-up activities in the form of teaching by applying the simulation method (Beavan et al, 2020;Krakauer et al, 2019;Li et al, 2020;Vanneste et al, 2021;Veldman et al, 2020). This is intended so that students can easily understand and accept the material presented by the teacher and in the end the students will better understand and master the basic techniques of playing table tennis.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Much of the knowledge base regarding physical activity and cognition in children centers on executive function and its relationship with physical activity. Data from cross-sectional studies and randomized controlled trials have indicated that physically active children possess greater executive function than their inactive counterparts [ 14 , 15 ], and interventional studies have indicated favorable changes in attributes of executive function (e.g., creativity) in response to varying forms of physical activity via physical education [ 16 ]. However, very few studies on physical activity and executive function have focused on a Latino school-aged population.…”
Section: Introductionmentioning
confidence: 99%